Linfoma gastrointestinal multicéntrico sucesivo - Piñeyro, Alberto; Torterolo, Edgardo; Bergalli, Luis (Cirugía del Uruguay, 1980)
A patient suffering from successive murticentric gastrointestinal lymphoma was treated successfully after 6 years through the association of surgery, telecobaltotherapy and chemiotherapy. The paper, furthermore, discusses extraganglionic forms of malignant lymphomas.